## Search

.## Management Sciences

A. 29

**B. 27**

C. 28

D. 7

Explanation:

Let the roots of the quadratic equation be x and 3x.

Sum of roots = -(-12) = 12

a + 3a = 4a = 12 => a = 3

Product of the roots = 3a2 = 3(3)2 = **27.**

### Related Mcqs:

- Find the roots of the quadratic equation: x2 + 2x – 15 = 0?

- A. -5, 3 B. 3, 5 C. -3, 5 D. -3, -5...

- Find the quadratic equations whose roots are the reciprocals of the roots of 2x

^{2}+ 5x + 3 = 0?

- A. 3x2 + 5x – 2 = 0 B. 3x2 + 5x + 2 = 0 C. 3x2 – 5x + 2 = 0 D. 3x2 – 5x – 2 = 0...

- Find the value of a/b + b/a, if a and b are the roots of the quadratic equation x

^{2}+ 8x + 4 = 0?

- A. 15 B. 14 C. 24 D. 26...

- I. a

^{2}– 13a + 42 = 0,

II. b

^{2}– 15b + 56 = 0 to solve both the equations to find the values of a and b?

- A. If a > b B. If a ≥ b C. If a < b D. If a ≤ b....

- Find the roots of quadratic equation: 3x

^{2}– 7x – 6 = 0?

- A. -6, 3 B. 3, -2/3 C. -5, 2 D. -9, 2...

## Recent Comments